2011
DOI: 10.1002/chem.201101654
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Hydrothermal Method to Prepare Carbon and Lanthanum Co‐Doped TiO2 Nanocrystals with Exposed {001} Facets and Their High UV and Visible‐Light Photocatalytic Activity

Abstract: TiO 2 crystals have attracted much attention due to their unique optical and electronic properties when compared to the bulk phase. They have already been applied to photocatalysis, photovoltaics, sensing, and photonic crystals. [1][2][3] Recently, TiO 2 crystals with exposed {001} facets have attracted a lot of attention due to their higher reactivity. [4][5][6][7] However, {001} facets usually diminish rapidly during the crystal growth process due to their higher energy.[8] Many research reports have concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…The former is primarily responsible for its visible light response. The surface carbon species also can produce some surface or subsurface Ti-C-O or Ti-O-C bonds to promote the generation of lattice defects [27].…”
Section: Uv-drs Electron Paramagnetic Resonance (Epr) and Xps Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The former is primarily responsible for its visible light response. The surface carbon species also can produce some surface or subsurface Ti-C-O or Ti-O-C bonds to promote the generation of lattice defects [27].…”
Section: Uv-drs Electron Paramagnetic Resonance (Epr) and Xps Studiesmentioning
confidence: 99%
“…Gu et al [26] prepared micro-mesoporous carbon-doped TiO 2 photocatalysts by a new low-temperature procedure (at a temperature as low as 60°C and without special equipment requirements), which exhibit perfect photo-catalytic activity under visible light irradiation. Xing et al [27] showed that the carbon doped into the TiO 2 lattice was conductive to the formation of impurity states inside the band gap of TiO 2 . And the decrease of energy level is beneficial to the absorption of visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental studies demonstrate that {0 0 1} facets of anatase TiO 2 is more reactive than the thermodynamically stable (1 0 1) facets, because of its special electronic and superficial structures [38]. The 2p states of the surface O atoms on the {0 0 1} facets are unstable and very reactive [38], which suggests more oxygen vacancies existing on the surface of {0 0 1} facets.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…Theoretical and experimental studies demonstrate that {0 0 1} facets of anatase TiO 2 is more reactive than the thermodynamically stable (1 0 1) facets, because of its special electronic and superficial structures [38]. The 2p states of the surface O atoms on the {0 0 1} facets are unstable and very reactive [38], which suggests more oxygen vacancies existing on the surface of {0 0 1} facets. The defects caused by oxygen vacancies can act as an activated center in the photocatalysis process due to the adsorption of OH [38], which leads to the high photocatalytic activities of N-TiO 2 and N,La-TiO 2 NSs under visible light.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation